Cloud Opacity Variations from Nighttime Observations in Venus Transparency Windows - Daria Evdokimova; Anna Fedorova; Nikolay Ignatiev; Mariya Zharikova; Oleg Korablev; Franck Montmessin; Jean-Loup Bertaux (Atmosphere)
The thick cloud layer enshrouding Venus influences its thermal balance and climate evolution. However, our knowledge of total optical depth, spatial and temporal variations in the clouds is limited. We present the first complete study of the SPICAV IR spectrometer observations in the 1.28- and 1.31-µm atmospheric transparency windows during the Venus Express mission in 2006–2014. The nadir spectra were analyzed with one-dimensional multiple scattering radiative transfer model to obtain the variability of total cloud opacity on the Venus night side. The optical depth recomputed to 1 µm averages 36.7 with a standard deviation of 6.1. Cloud opacity depends on latitude, with a minimum at 50–55° N. In the Southern Hemisphere, this latitude dependence is less pronounced due to the reduced spatial resolution of the experiment, determined by the eccentricity of the spacecraft’s orbit. Cloud opacity exhibits strong variability at short time scales, mostly in the range of 25–50. The variability is more pronounced in the equatorial region. The lack of imaging capability limits the quantitative characterization of the periodicity. No persistent longitude or local time trends were detected.